Gender Differences Regarding the Ability to Think Critically in High School Biology Subjects during the Covid-19 Pandemic - Siti Chaliza Harun; Hasruddin Hasruddin (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The ability of critical thinking is very important to have. If the students have an ability of critical thinking, they students can solve the problems that facing them on the lesson study especially biology. This study aims to determine students critical thinking skills based on the gender of high school biology subjects during the Covid-19 pandemic. The data were analyzed descriptively with a quantitative approach. The population in this study was all students of class XII science high school. The sample of this research was taken by simple random sampling by means of lottery as many as 35 students. The results showed that the average value of women’s critical thinking skills was 77 and was in the medium criteria. While the average value of male critical thinking skills is 64 and is in the low criteria. It can be concluded that the ability to think critically based on gender is higher for female students than male students. From the test result show the value of sig. (2-tailed) obtained t count of 2.118 sig at 0.042 which means that there is a significant difference in critical thinking ability of male and female students.Abstract Kemampuan berpikir kritis sangat penting dimiliki. Jika siswa sudah memiliki kemampuan berpikir kritis, siswa dapat memecahkan persoalan-persoalan yang dihadapi dalam pelajaran terutama dalam pelajaran Biologi. Penelitian ini bertujuan untuk mengetahui kemampuan berpikir kritis siswa berdasarkan gender mata pelajaran biologi SMApada masa pandemi covid 19. Data dianalisis secara deskriptif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh siswa kelas XII IPA SMA. Sampel penelitian ini diambil secara simple random sampling dengan cara undian sebanyak 35 siswa.Hasil penelitian menunjukkan bahwa rata-rata nilai kemampuan berpikir kritis perempuan 77 dan berada pada kriteria sedang. Sementara rata-rata nilai kemampuan berpikir kritis laki-laki 64 dan berada pada kriteria rendah. Maka dapat disimpulkan bahwa kemampuan berpikir kritis berdasarkan gender lebih tinggi siswa perempuan daripada siswa laki-laki. Dari hasil pengujian menunjukkan nilai sig. (2-tailed) diperoleh t hitung sebesar 2,118 sig pada 0,042 yang artinya terdapat perbedaan yang signifikan kemampuan berpikir kritis pada siswa laki-laki dan perempuan.